Evaluation of anthelmintic activity of Meyna spinosa Roxb. – A folk medicinal plant of Northeast India - Saikat Sen; Jasmin Ara; Raja Chakraborty; Pratap Kalita (Journal of Traditional and Folk Practices (JTFP), 2018)
Natural antiparasitics have exhibited cabbalistic effects in healthcare units since ancient time. Meyna spinosa Roxb. is a traditional medicinal plant of North east India and is used in the treatment of different worm infections. The present study was designed to investigate in vitro anthelmintic activity of the methanolic extract of Meyna spinosa against Indian adult earthworm (Pheretima posthuma). Worm motility and mortality were assessed in order to evaluate the anthelmintic activity of the extract. Paralysis time and time of death of worms was noted in the presence of different concentrations of extract (50 mg/mL, 100 mg/mL, and 150 mg/mL) and standard drug, albendazole. The results showed the extract exhibited significant in vitro anthelmintic activity against P. posthuma at different concentrations. Extract (150 mg/mL) exhibited very strong anthelmintic effect which was evidenced by the paralysis and death of worms in lesser time. In conclusion, the findings revealed that the methanolic extract of Meyna spinosa leaves has effective anthelmintic activity against P. posthuma and indicated that the plant may be a potent natural antiparasitic agent.